Virtue Epistemology Naturalized
VI, 360 p. 6 illus.
Keywords: This book presents four bridges connecting work in virtue epistemology and work in philosophy of science (broadly construed) that may serve as catalysts for the further development of naturalized virtue epistemology. These bridges are: empirically informed theories of epistemic virtue; virtue theoretic solutions to underdetermination; epistemic virtues in the history of science; and the value of understanding. Virtue epistemology has opened many new areas of inquiry in contemporary epistemology including: epistemic agency, the role of motivations and emotions in epistemology, the nature of abilities, skills and competences, wisdom and curiosity. Value driven epistemic inquiry has become quite complex and there is a need for a responsible and rigorous process of constructing naturalized theories of epistemic virtue. This volume makes the involvement of the sciences more explicit and looks at the empirical aspect of virtue epistemology. Concerns about virtue epistemology are considered in the essays contained here, including the question: can any virtue epistemology meet both the normativity constraint and the empirical constraint? The volume suggests that these worries should not be seen as impediments but rather as useful constraints and desiderata to guide the construction of naturalized theories of epistemic virtue.